Exploring the Challenges in Covering Dental Services through Complementary Insurance in Iran: A Qualitative Study - Zahra Pouraskari; Reza Yazdani; Hossein Hessari (Hindawi Limited, 2024)
Background. Financial protection is crucial for attaining universal health coverage. The inclusion of costly dental services in insurance plans poses a significant challenge for all parties involved in the insurance sector. This study aimed to investigate the challenges of covering dental services by complementary insurance in Iran during 2020-2021. Materials and Methods. This qualitative research was conducted in Iran during 2020-2021. A triangulation of methods and data sources were employed to achieve a comprehensive perspective. In-depth semistructured interviews were conducted on an individual basis, and all national documents, rules, regulations, and instructions pertaining to complementary dental insurance were thoroughly reviewed. Purposeful sampling was used to select participants from all stakeholder groups engaged in dental insurance coverage, including (1) health system policymakers, (2) insurers, (3) policyholders, (4) care providers (dentists), and (5) insured people. Six open-ended questions were formulated to explore various facets of dental insurance, including (1) development, (2) management, (3) population coverage, (4) premium calculation, (5) services coverage, and (6) payment and reimbursement mechanisms. With the consent of the participants, all interviews were recorded and transcribed verbatim. The gathered data were evaluated using a framework analysis approach in the MAXQDA20 software. Finally, the primary themes, each encompassing multiple subthemes, were identified and presented. Results. A total of 26 interviews were conducted with five groups of interviewees, and nine national documents were evaluated. Six themes were extracted, which included 18 codes from the interviews and seven codes from the documents. The extracted themes were as follows: (1) Insurance commitments and service coverage, (2) reimbursement system, (3) information system, (4) economic issues, (5) population coverage, and (6) regulation and supervision. The high cost of dental services was the most frequent challenge, followed by the insurance commitments and service coverage. Conclusions. The delivery of dental services through complementary insurance in Iran primarily faces economic and service coverage challenges. The resolution hinges on the collaboration between basic and complementary insurance sectors, the development of a unified information system for insured individuals, and the implementation of a risk-adjusted premium plan.